2016
DOI: 10.1038/srep25663
|View full text |Cite
|
Sign up to set email alerts
|

CSF1R blockade slows the progression of amyotrophic lateral sclerosis by reducing microgliosis and invasion of macrophages into peripheral nerves

Abstract: Inflammation is a common neuropathological feature in several neurological disorders, including amyotrophic lateral sclerosis (ALS). We have studied the contribution of CSF1R signalling to inflammation in ALS, as a pathway previously reported to control the expansion and activation of microglial cells. We found that microglial cell proliferation in the spinal cord of SOD1G93A transgenic mice correlates with the expression of CSF1R and its ligand CSF1. Administration of GW2580, a selective CSF1R inhibitor, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
155
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(167 citation statements)
references
References 45 publications
11
155
0
1
Order By: Relevance
“…[17][18][19] Here, we provide novel evidence that CSF1R signaling may likewise contribute to microglial proliferation and neuroinflammation in PD, as evidenced by increased levels of the ligand CSF-1 in postmortem PD patients, along with increased mRNA and protein levels of CSF1R, CSF-1, and IL-34 in animal models of PD. [17][18][19] Here, we provide novel evidence that CSF1R signaling may likewise contribute to microglial proliferation and neuroinflammation in PD, as evidenced by increased levels of the ligand CSF-1 in postmortem PD patients, along with increased mRNA and protein levels of CSF1R, CSF-1, and IL-34 in animal models of PD.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…[17][18][19] Here, we provide novel evidence that CSF1R signaling may likewise contribute to microglial proliferation and neuroinflammation in PD, as evidenced by increased levels of the ligand CSF-1 in postmortem PD patients, along with increased mRNA and protein levels of CSF1R, CSF-1, and IL-34 in animal models of PD. [17][18][19] Here, we provide novel evidence that CSF1R signaling may likewise contribute to microglial proliferation and neuroinflammation in PD, as evidenced by increased levels of the ligand CSF-1 in postmortem PD patients, along with increased mRNA and protein levels of CSF1R, CSF-1, and IL-34 in animal models of PD.…”
mentioning
confidence: 70%
“…49 Class III receptor tyrosine kinases, which includes CSF1R, c-kit, PDGFRβ, and FLT3, all regulate cell survival through downstream pathways such as PI3K and Akt. [17][18][19] GW2580 completely blocked the MPTP-induced gene expression of Iba1 in the mouse striatum, along with significant reduction of Iba1 + and Ki-67 + / Iba1 + cells in the SN (Figure 4). 21,50,51 Recent research found that complete ablation of microglia in the brain using PLX-3397 exacerbated MPTPinduced neuroinflammation, neurotoxicity, and behavioral effects.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In the CNS, ALS is typically accompanied by neuroinflammation involving the emergence of reactive microglia, astrocytes, and aberrant glial phenotypes (3)(4)(5). Evidence also shows activation of circulating immune cells (6), as well as immune cell infiltration of the ALS-degenerating peripheral nerves containing motor axons (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that aberrant microglial cells from symptomatic ALS rats are responsive to M-CSF through the tyrosine kinase receptor CSF-1R [10]. Accordingly, the pharmacological inhibition of CSF-1R decreases microglia reactivity and extends the life span of ALS mice [10,19]. Astrocytes are another major source of M-CSF and IL-34, both factors being potent agonists of the CSF-1R [20,21].…”
Section: Discussionmentioning
confidence: 99%